Recent Advancement in mRNA Vaccine Development and Applications - Nojoud Al Fayez; Majed S. Nassar; Abdullah A. Alshehri; Meshal K. Alnefaie; Fahad A. Almughem; Bayan Y. Alshehri; Abdullah O. Alawad; Essam A. Tawfik (MDPI AG, 2023)
Messenger RNA (mRNA) vaccine development for preventive and therapeutic applications has evolved rapidly over the last decade. The mRVNA vaccine has proven therapeutic efficacy in various applications, including infectious disease, immunotherapy, genetic disorders, regenerative medicine, and cancer. Many mRNA vaccines have made it to clinical trials, and a couple have obtained FDA approval. This emerging therapeutic approach has several advantages over conventional methods: safety; efficacy; adaptability; bulk production; and cost-effectiveness. However, it is worth mentioning that the delivery to the target site and in vivo degradation and thermal stability are boundaries that can alter their efficacy and outcomes. In this review, we shed light on different types of mRNA vaccines, their mode of action, and the process to optimize their development and overcome their limitations. We also have explored various delivery systems focusing on the nanoparticle-mediated delivery of the mRNA vaccine. Generally, the delivery system plays a vital role in enhancing mRNA vaccine stability, biocompatibility, and homing to the desired cells and tissues. In addition to their function as a delivery vehicle, they serve as a compartment that shields and protects the mRNA molecules against physical, chemical, and biological activities that can alter their efficiency. Finally, we focused on the future considerations that should be attained for safer and more efficient mRNA application underlining the advantages and disadvantages of the current mRNA vaccines.